2013
DOI: 10.1136/tobaccocontrol-2013-051185
|View full text |Cite
|
Sign up to set email alerts
|

Forensic analysis of online marketing for electronic nicotine delivery systems

Abstract: These findings support increased monitoring and regulation of ENDS marketing to prevent deceptive marketing tactics and ensure consumer safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…Disposables are ready to use out of the package, whereas kits allow consumers to reuse components and contain a rechargeable battery, charger, and cartridge refill (Lorillard Technologies, 2013;White Cloud Electronic Cigarettes, 2013). Replacement cartridges are also available in a variety of flavors (Cobb, Brookover, & Cobb, 2013;Wollscheid & Kremzner, 2009). E-cigarettes have been marketed to tobacco smokers as a cessation aid (Food and Drug Administration, 2013) and for use in places where smoking is restricted (Benowitz & Goniewicz, 2013;Henningfield & Zaatari, 2010;Richardson, Ganz, Stalgaitis, Abrams, & Vallone, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disposables are ready to use out of the package, whereas kits allow consumers to reuse components and contain a rechargeable battery, charger, and cartridge refill (Lorillard Technologies, 2013;White Cloud Electronic Cigarettes, 2013). Replacement cartridges are also available in a variety of flavors (Cobb, Brookover, & Cobb, 2013;Wollscheid & Kremzner, 2009). E-cigarettes have been marketed to tobacco smokers as a cessation aid (Food and Drug Administration, 2013) and for use in places where smoking is restricted (Benowitz & Goniewicz, 2013;Henningfield & Zaatari, 2010;Richardson, Ganz, Stalgaitis, Abrams, & Vallone, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarettes have been marketed to tobacco smokers as a cessation aid (Food and Drug Administration, 2013) and for use in places where smoking is restricted (Benowitz & Goniewicz, 2013;Henningfield & Zaatari, 2010;Richardson, Ganz, Stalgaitis, Abrams, & Vallone, 2013). Manufacturers claim e-cigarettes are more cost-effective and socially acceptable compared with conventional cigarettes (Cobb et al, 2013;Pozin, 2013). Although e-cigarettes will be regulated as tobacco products, the FDA has yet to issue rules that will impact how Advance Access publication May 20, 2014 they are advertised and promoted (Tobacco Control Legal Consortium, 2013), thus providing opportunities for manufacturers to access mainstream outlets.…”
Section: Discussionmentioning
confidence: 99%
“…E-cigarettes have a strong online presence (Cobb, Brookover, & Cobb, 2013;Yamin, Bitton, & Bates, 2010), which helps to explain why more than one-quarter of smokers learned about e-cigarettes online. The Internet may play an important role by reinforcing word-of-mouth messages, providing additional information as follow-up to personal conversations, or priming people to participate in conversations about e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 If smokers switch completely from smoking combustible cigarettes to e-cigarettes, they could be reducing their risks of developing smoking-related illnesses. However, despite many users claiming to use e-cigarettes to quit or reduce smoking, [5][6][7][8][9] a recent meta-analysis showed that in population-based studies, smokers who use e-cigarettes were less likely than those who do not use e-cigarettes to be successful in quitting smoking.…”
Section: Trends In Awareness Use Of and Beliefs About Electronic CImentioning
confidence: 99%